Seasonal photosynthesis, respiration, and calcification of a temperate Maërl bed in southern Portugal - SORDO, LAURA (2020)
Rhodolith (maerl) beds are biodiversity hotspots with a worldwide distribution. Maerl is the general term for free-living non-geniculate rhodoliths or coralline red algae. In southern Portugal, maerl beds are mainly composed of Phymatolithon lusitanicum, recently identified as a new species and commonly misidentified as Phymatolithon calcareum. Photosynthesis, respiration, and growth rates of the algae were measured seasonally, as well as the photosynthetic pigment composition. To characterize the seasonal and interannual patterns of key abiotic conditions in the largest described maerl bed of the Portuguese coast, temperature, irradiance, and dissolved oxygen were continuously monitored over a 2-year period. At the bed depth (22 m), temperature ranged between 14 degrees C in winter and 24 degrees C in summer, irradiance varied from 5 to 75 mu.mol m(-2) s(-1) , and dissolved oxygen from 5.8 to 7.25 mg O-2 L-1. We found a strong linear relationship (r(2) = 0.95) between gross primary production (GPP) and relative electron transport rates (rETRs). Both methods led to similar results and an average molar ratio of 0.24. Photosynthesis and respiration increased in summer and decreased in autumn and winter. In the summer of 2013, the growth rates were twofold higher (1.34 mu.mol CaCO3 g(-1) day(-1)) than in the other seasons. In winter and spring, to compensate for light deprivation and low temperature, algae increased their chlorophyll a and carotenoid concentrations while also decreasing their phycobilin concentration, in this case probably due to nutrient limitation. To isolate the role of temperature on the algae's metabolism, the photosynthetic and respiration rates of individual thalli were measured at eight different temperatures in the laboratory (from 12 degrees C to 26 degrees C). Phymatolithon lusitanicum photosynthesis increased twofold after a threshold of 18 degrees C (from 2.2 at 18 degrees C to 3.87 mu mol O-2 m(-2) s(-1) at 20 degrees C), whereas respiration increased fourfold with temperature after a threshold of 22 degrees C (from -0.38 at 18 degrees C to -1.81 (mu mol O-2 m(-2) s(-1) at 24 degrees C). The significant increases on respiration, photosynthetic rates, and maximum growth with temperature reveal that the metabolic rates of P. lusitanicum are highly sensitive to ocean warming.